The study of the sacred as a humanistic horizon: On the Mircea Eliade’s approach in the History of Religions - Yahyaoui, Yassine (Münster journal for Islamic and philosophical studies, 2022)
The aim of this research is to‭ ‬highlight the importance of the academic study of the sacred in the field of the history of religions‭, ‬and its impact on opening a new humanistic horizon that allows to overcome the dilemma of religious violence‭. ‬In this paper‭, ‬I based on what the historian of religions Mircea Eliade presented in his study of the religious phenomenon‭, ‬whether in the dialectic of the sacred and the‭ ‬profane‭, ‬or in his attempt to answer the contemporary human crisis‭; ‬especially since the quest for a new humanism is considered‭ ‬as the cornerstone that brings coherence to all of Eliade’s work‭. ‬The problematic question of the paper can then be defined as follows‭: ‬How can Eliade’s approach to the study of religions open the horizon for a new humanism‭?‬